PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, TOTAL ASSET TURN OVER, RETURN ON EQUITY, DAN EARNING PER SHARE TERHADAP DIVIDEND PAYOUT RATIO (Studi pada Perusahaan Real Estate, Property dan Konstruksi yang Terdaftar di Bursa Efek Indonesia Periode 2011-20 - Sri Rizal Iswari, 12.05.51.0014; Irsad, Moch (Students Journal of Economic and Management, 2016)
This study aims to prove the influence of Current Ratio, Debt to Equity Ratio, Total Assets Turn over, Return on Equity and Earning Per Share Dividend Payout Ratio. Population used in this study are all companies in the real estate sector and property and construction. Samples were taken by using purposive sample thus obtained a sample of 20 companies. Methods of analysis of this study using multiple linear regression analysis. The results showed that of all the independent variables is Current Ratio, Debt to Equity Ratio, Total Assets Turn over, Return on Equity and Earning Per Share, only the Earning Per Share which is a positive and significant impact on the Dividend Payout Ratio. While the Return on Equity which is a negative effect on the Dividend Payout Ratio. Keywords : Current Ratio , Debt to Equity Ratio , Total Assets Turn over , Return on Equity , Earnings Per Share Dividend Payout Ratio.